2019
DOI: 10.1002/bjs.11079
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node biopsy in microinvasive ductal carcinomain situ

Abstract: Background: Microinvasive breast cancer is an uncommon pathological entity. Owing to the rarity of this condition, its surgical axillary management and overall prognosis remain controversial.Methods: A database was analysed to identify patients with microinvasive ductal carcinoma in situ (DCIS) who had surgery for invasive breast cancer at the European Institute of Oncology, Milan, between 1998 and 2010. Women who had undergone axillary staging by sentinel lymph node biopsy were included in the study.Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 55 publications
2
30
0
Order By: Relevance
“…Furthermore, a small rate of SLN metastases in microinvasive BC (2.9%) was also described by Fan et al, who studied a wide cohort from a National Cancer Database [55] . Indeed, these observations are supported by Level 1 evidence underlining that axillary dissection may be avoided in SLN-positive breast cancer patients undergoing BCS with radiotherapy when there is a low axillary metastatic burden (Z0011) [52] . As outlined through this historical perspective, the common thread from the past that weaves its way through the present and stretches toward the future is the progressive tendency to reduce the extension of axillary lymph-node surgery in breast cancer management ( Figs.…”
Section: Looking Toward the Futurementioning
confidence: 88%
See 2 more Smart Citations
“…Furthermore, a small rate of SLN metastases in microinvasive BC (2.9%) was also described by Fan et al, who studied a wide cohort from a National Cancer Database [55] . Indeed, these observations are supported by Level 1 evidence underlining that axillary dissection may be avoided in SLN-positive breast cancer patients undergoing BCS with radiotherapy when there is a low axillary metastatic burden (Z0011) [52] . As outlined through this historical perspective, the common thread from the past that weaves its way through the present and stretches toward the future is the progressive tendency to reduce the extension of axillary lymph-node surgery in breast cancer management ( Figs.…”
Section: Looking Toward the Futurementioning
confidence: 88%
“…In the future, could we consider a potential omission of SLNB in selected cases of MIC? The incidence of axillary metastasis in sentinel nodes in MIC varies in studies from approximately 2% to 20% [52] . In a recent retrospective study from the European Institute of Oncology, that analyzed 257 women with microinvasive breast cancer who underwent SLNB, the reported incidence of axillary metastasis was 12.1%, slightly higher than previously reported [53] , and which falls within the range described in the published medical literature [52] .…”
Section: Looking Toward the Futurementioning
confidence: 99%
See 1 more Smart Citation
“…Patients with negative SLNB do not require further surgical management of the axilla. However, in a recent study investigating the role of SLNB in DCIS-MI, Magnoni and colleagues 33 found that SLNB was not a good predictor of the need for ALND. Among 257 women with microinvasive breast cancer, 87.9% (266) had negative SLNB, and 12.1% (31) had positive SLNB.…”
Section: Management Of Axillary Lymph Nodes Dcis-mimentioning
confidence: 95%
“…[51][52][53] Even if the SLN is found positive in patients with a preoperative diagnosis of DCIS, it is most frequently reported to present as micrometastases (defined as small metastases sized 0.2-2.0 mm), which are of limited clinical value in this respect. 54,55 Nowadays, a delayed SLNB following lumpectomy if invasive cancer is shown, is considered a feasible option. Therefore, we agree with a recent study by Van Roozendaal et al who suggest omitting SLNB completely in patients with DCIS undergoing BCS.…”
Section: General Discussion and Future Perspectivesmentioning
confidence: 99%